Life history and DNA barcode of Oxyurella longicaudis (Birgei, 1910) (Cladocera, Anomopoda, Chydoridae) - Almeida Castilho, Maria Carolina de [UNESP]; Santos Wisniewski, Maria Jose dos; Abreu, Cnthia Bruno de; Orlando, Tereza Cristina (Springer, 2015)
Background: Cladocera is an important group of freshwater zooplankton, and the species plays an important role in energy transfer and in aquatic food webs. Oxyurella longicaudis is a Chydoridae species that has been recorded in North and South America. The aim of this study is to investigate the life cycle aspects of parthenogenetic females of O. longicaudis cultured in laboratory under controlled conditions: temperature (23 degrees C +/- 05 degrees C), photoperiod (12 h light/12 h dark), food supply, and reconstituted water.Results: Embryonic development duration (2.3 +/- 0.5 days), post-embryonic development (5.2 +/- 0.69 days), mean fecundity (two eggs female(-1) brood(-1)), total egg production (22.55 +/- 3.98 eggs), average longevity (58 days), and body growth of the species were recorded. We also report the first DNA barcode for O. longicaudis isolated in Brazil, which will allow for easy identification in future zooplankton community studies. The analysis shows a genetic divergence of around 7% between our Brazilian isolate and O. longicaudis isolates from Mexico.Conclusions: The time of embryonic and post-embryonic development of O. longicaudis was higher than that of the other species of the same family, which contributed to lower total egg production throughout its life cycle. The genetic divergence appears to be sufficient to classify the two isolates as different species.
Keywords: Conservation-priority areas; Zooplankton; Bionomics; Cryptic speciation; COI